Neurexins and their ligands at inhibitory synapses - Boxer, Emma E.; Aoto, Jason (Frontiers in Synaptic Neuroscience, 2022)
Since the discovery of neurexins (Nrxns) as essential and evolutionarily conserved synaptic adhesion molecules, focus has largely centered on their functional contributions to glutamatergic synapses. Recently, significant advances to our understanding of neurexin function at GABAergic synapses have revealed that neurexins can play pleiotropic roles in regulating inhibitory synapse maintenance and function in a brain-region and synapse-specific manner. GABAergic neurons are incredibly diverse, exhibiting distinct synaptic properties, sites of innervation, neuromodulation, and plasticity. Different classes of GABAergic neurons often express distinct repertoires of Nrxn isoforms that exhibit differential alternative exon usage. Further, Nrxn ligands can be differentially expressed and can display synapse-specific localization patterns, which may contribute to the formation of a complex trans-synaptic molecular code that establishes the properties of inhibitory synapse function and properties of local circuitry. In this review, we will discuss how Nrxns and their ligands sculpt synaptic inhibition in a brain-region, cell-type and synapse-specific manner.